ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING (Studi pada Perusahaan Manufaktur yang Listed di BEI Tahun 2008 – 2011) - Alivia, Natasha Rizky; M. Chabachib, M. Chabachib (Faculty of Economics and Business Diponegoro University, 2013)
Firm Value is one of the factors are considered by investors for making investment decisions. Research of the factors that affect the firm value still shows the differences in researchoutcomes. Also based on the data available, there are differences regarding the direction of the relationship factors that influence the firm value. Therefore, it still needs to be done further research on the factors that affect the firm value. This study examined the effect of Total AssetTurnover (TATO), Sales growth (SG), Net Profit Margin (NPM) on Return on Assets (ROA) and the influence of Total Asset Turnover (TATO), Return on Assets (ROA), Net Profit Margin (NPM)of the Price Book Value (PBV) in the manufacturing companies listed on the Indonesia StockExchange (BEI) in the period from 2008 to 2011.The sample used in this study consisted of 71 manufacturing companies listed on theIndonesia Stock Exchange (BEI) in the period from 2008 to 2011. Sampling was done by purposive sampling method. Data obtained from the Indonesian Capitan Market Directory (ICMD) and the Annual Report of the company. The analysis technique used is multiple regression analysis and Path Analysis with the help of SEM.The results showed that the Total Asset Turnover (TATO) significant positive effect on return on assets (ROA) and Price Book Value (PBV .Based on Path Analysis Total Asset Turnover(TATO) indirectly influence the Price Book Value (PBV) through the Return on Assets (ROA).Sales growth (SG)have no significant negative effect on Return on Assets (ROA). Net Profit Margin(NPM) a positive effect on return on assets (ROA) and negative effect on Price Book Value (PBV).Based on Path analysis Net Profit Margin (NPM) indirectly influence the Price Book Value trough the Return on Asset (ROA)